1378The effect of vitamin D supplementation on acute respiratory infection -analysis of the D-Health Trial. (2nd September 2021) - Pham, Hai; Waterhouse, Mary; Baxter, Catherine; Romero, Briony; McLeod, Donald; Armstrong, Bruce; Ebeling, Peter; English, Dallas; Hartel, Gunter; Kimlin, Michael; Martineau, Adrian; O'Connell, Rachel; et al.
Abstract: Background: Observational studies link vitamin D deficiency with acute respiratory tract infection (ARTI) but results from randomised controlled trials are heterogeneous. Methods: We used data from The D-Health Trial (N = 21, 315); ARTI was a pre-specified trial outcome. Participants were men and women aged 60 to 79 years (with volunteers aged up to 84 years), supplemented with monthly doses of 60, 000 international units of vitamin D and followed for up to 5 years. Participants were asked to report occurrence of ARTI over the previous month via annual surveys, and a subset of participants completed 8-week respiratory symptom diaries in winter. We used regression models to estimate odds ratios, rate ratios and rate differences. Results: Vitamin D supplementation did not reduce the risk of ARTI (survey OR 0.98, 95% CI 0.93 to 1.02; diary OR 0.98, 95% CI 0.83 to 1.15). Analyses of diary data showed that vitamin D reduced the average duration by 0.5 days (95% CI 0.2 to 0.7 days) and the average number of days with severe symptoms by 0.4 days (95% CI 0.3 to 0.6 days). Conclusions: Monthly bolus doses of 60, 000 IU of vitamin D did not reduce the overall risk of ARTI but slightly reduce the duration of symptoms in the general population. Key messages: The reduction in the duration of symptoms suggests a potential impact of vitamin D on the immune response to infection.